An Analysis of Verbal and Nonverbal Communication Skill - Amanda, Aulia; Lestari, Indah (Indonesian Journal of ELT and Applied Linguistics, 2024)
Mata Najwa is a talk show program broadcasted by Metro TV in an interview format. In every interview, the interviewer's communication skills play an important role in determining the success of the program. Effective communication techniques on television aim to dig up information and provide entertainment, so that good communication skills are needed so that the interview runs smoothly and is interesting for the audience. The topics raised in the Mata Najwa program provide inspiration and insight to the audience. This program is considered to have higher quality than other talk shows, with various themes covering social, economic, and inspirational aspects. This study focuses on the episode "Habibie & Suara Putra Negeri" from Mata Najwa. This episode was chosen because it has inspirational value and provides social insight, although it is not directly related to formal education. The problem studied in this study is how the verbal and nonverbal communication techniques used by Najwa Shihab in the episode. The purpose of the study was to understand the communication approach applied by Najwa Shihab during the interview in the episode "Habibie & Suara Putra Negeri." This research approach uses a qualitative descriptive method. Based on the results of the study, it was found that Najwa Shihab uses a lot of persuasive communication techniques as the main strategy. In addition, other techniques such as instructive, informative, and humanistic are also used in the interview. Persuasive communication techniques can be seen from Najwa's use of verbal language that encourages and convinces the interviewee to provide answers according to the direction of the conversation. Najwa also succeeded in creating a comfortable atmosphere so that the interviewee tends to be open and answer every question asked. The nonverbal language used by Najwa Shihab in this episode includes supporting the chin, leaning the body, and repeated hand movements. Meanwhile, nonverbal language that appears less frequently includes nodding the head, smiling, shaking hands, frowning, body movements, eyebrow movements, eye movements, and maintaining a professional appearance. From this study, it can be concluded that Najwa Shihab predominantly uses persuasive communication techniques in the episode "Habibie & Suara Putra Negeri." Verbal language that persuades and encourages the interviewee to respond according to the interviewer's expectations is Najwa Shihab's characteristic. Nonverbal language such as supporting the chin, leaning the body, and hand movements are often used to strengthen effective communication and attract the audience's attention.